Diálogo entre Pré-existência e Intervenção Contemporânea: Estudo de cinco casas burguesas do Porto - Maria Leonor de Albuquerque Dunões (2015)
The historic center of Porto, UNESCO World Heritage Site, is being objectof several interventions, as well as adjacent areas. However the existence of manyvacant buildings, mostly single family homes, namely bourgeois houses, which arestill nowadays relevant elements of the various stages of the evolution of the city.Being currently urban intervention an unavoidable issue for the safeguardof the historical heritage, there is a need to explore the adaptability of this typeof buildings, which have been built in another era and for other uses, whilemaintaining its identity.The completion of traineeship in architectural studio addressed theauthor's interest to the solutions currently adopted in the interventions made inthe bourgeois houses of Porto. As such, the dissertation is developed following astudy aimed to the comprehension of the dialogue between the existing buildingand the contemporary intervention in these buildings.This thesis develops a study on five different interventions and thesolutions adopted to overcome the problems of bourgeois houses as: the lack ofnatural lighting indoors, the shortage of complete bathroom and thermal andacoustic comfort, as well as the absence of garage and lift.The case studies were selected to encompass a wide range of solutions,allowing the study of adaptability of these houses in different contexts that isfrequently limited by the decay of de pre-existence. These cases have been chosenin order to encompass different degrees of intervention, types of bourgeois housesand uses. On the other hand, the choice was determined by the availability ofinformation provided by the architects, so it could be possible to attain a balancedstudy of all cases.Thus, this thesis is presented as a study that gives an overview aboutcurrent interventions made in bourgeois houses and intends to demonstrate anumber of possible and differentiated solutions to that can be used to overcomethe main problems.